Productivity Analysis of Milkfish Farming in Areas Surrounding Mines in Tinanggea District, South Konawe Regency - Dian Balqis Zulaika; Muhammad Aswar Limi; Wa Ode Yusria (International journal of technology and education research, 2025)
This study aims to determine 1) the productivity of milkfish farming in mining-affected areas, and 2) the income and revenue from the productivity of milkfish farming in mining-affected areas in Tinanggea District, South Konawe Regency. The research was conducted in Wadonggo Village, Tinanggea District, South Konawe Regency, Southeast Sulawesi Province. The research took place from March to June 2024. The population in this study consisted of all milkfish pond farmers around the mine in Wadonggo Village, Tinanggea District, South Konawe Regency, totaling 41 people. The sampling technique used in this study was saturated sampling, which is a sampling technique where all members of the population are used as samples, resulting in a sample size of 41 people. The data analysis used includes farming productivity analysis and income analysis. The results of the study indicate that the productivity of milkfish farming in mining-affected areas in Wadonggo Village, Tinanggea District, reached 1,363.63 kg/ha/season. This productivity reflects the farmers' efforts in applying efficient farming techniques and the appropriate use of inputs to support the growth of milkfish. The average income of milkfish pond farmers in Wadonggo Village is IDR 56,485,165/season. This substantial net income indicates the effectiveness and efficiency of pond operations, as well as the high profitability potential of milkfish farming in this area